Biomaterials for dental implants: The Basics Revisited - Dhull, Kanika Singh; Jain, Nikil Kumar; M S, Girish; Das, Debasmita; Devraj, Indira Mysore; Rai, Sajni (Bangladesh Journal of Medical Science, 2026)
Numerous studies conducted over many years have provided us with knowledge on a variety of biomaterials used as dental implants. A biomaterial is a substance that has been created to take on a structure that may be employed, either alone or as a component of a complex system, to regulate interactions with elements of living systems and therefore to control the course of any therapeutic or diagnostic operation. The need for biomaterials that are not only mechanically or chemically appropriate but also biocompatible with the oral environment has been driven by the growing awareness of dental implants as a restoration method for lost teeth. This article provides insight into the many traditional biomaterials, including titanium implants, which have only recently been introduced and are becoming more and more common. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S11-S17